2007
DOI: 10.1016/j.rmed.2006.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for ventilator-associated pneumonia in a developing country: Where is the difference?

Abstract: The epidemiologic profile of VAP in terms of incidence, length of stay and clinical course resembles the general pattern described everywhere. Surprisingly, we could not identify any potentially modifiable risk factor for VAP. A comprehensive multicenter study is warranted. It should provide deep insight about the specific microbiological, genetic and clinic features of VAP in our setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 35 publications
4
17
0
4
Order By: Relevance
“…This is another likely cause of the higher rate of VAP in our department than in high‐income countries. The incidences of VAP in our study were similar to rates reported in other developing countries, including India and Colombia . Differences in cultural heritage, health services and clinical research development may play roles in the differences in occurrence of VAP between developing countries and developed nations, and require further investigation.…”
Section: Discussionsupporting
confidence: 83%
“…This is another likely cause of the higher rate of VAP in our department than in high‐income countries. The incidences of VAP in our study were similar to rates reported in other developing countries, including India and Colombia . Differences in cultural heritage, health services and clinical research development may play roles in the differences in occurrence of VAP between developing countries and developed nations, and require further investigation.…”
Section: Discussionsupporting
confidence: 83%
“…61 It accounts for 62-73% of all cases, with the highest daily hazard rates of 2-4% reported to occur between days 6 and 8. [61][62][63] Whether VAP can be eradicated requires discussion of both VAP pathophysiology and ETT design limitations. To begin with, terms such as VAP and VAE are unfortunate misnomers.…”
Section: Pathophysiology Of Ventilator-associated Pneumoniamentioning
confidence: 99%
“…Late-onset VAP accounts for both the majority of cases and the greatest associated morbidity and mortality, 61 with the highest risk occurring between days 6 and 8 of mechanical ventilation. [61][62][63] In the early 1990s, the average duration of mechanical ventilation was 7-12 d, with an additional average of 3-5 d for weaning using various techniques driven by protocols. 99 In a contemporaneous survey of clinicians, the average duration of weaning ranged from 5 to 18 d, with the longest duration associated with synchronized intermittent mandatory ventilation combined with pressure support ventilation.…”
Section: Weaning and Sedation Strategiesmentioning
confidence: 99%
“…VAP give a bad impact for patients, family, even healthcare institution (hospital) because VAP could prolongs duration of ventilator and prolongs hospital stay until 7-9 days with mortality rate over 50%. Each of patient with VAP drives up hospital cost between $10.019-$13.647 for diagnostic and medicine (Galal, 2016;Jaimes, La, Go, Mu, & Ramı, 2007;Klompas et al, 2014;Teo, 2012;Wiryana, 2007).…”
Section: Introductionmentioning
confidence: 99%